Global cyclic queuing and forwarding mechanism for large-scale deterministic networks - Yijun MO; Zihan YANG; Huiyu LIU; Tianliu HE (Dianxin kexue)
Delay and jitter sensitive industrial control and remote driving application-driven network by best-effort to deterministic service.To meet the deterministic application of delay and jitter demands, industry and academia have conducted detailed research on stream filtering shaping and queue forwarding control, implementing microsecond delay and microsecond jitter of light load steady in small-scale ethernet environment.However, the study seldom considers the effects of long-distance topology change, transmission delay fluctuations and short-time traffic overloads, challenging to meet deterministic requirements under large-scale backbone networks.For this challenge, based on cyclic queuing and forwarding, considers source-destination path properties and deterministic traffic intensity, the global cyclic queuing and forwarding three-queue was proposed.The deterministic network simulation system was based on OMNeT++.Experiments compare queue forwarding control mechanisms such as CQF, CQF-three and GCQF-three.Results show that GCQF-three can timely adjust the gatecontrol and queueing priority according to the deterministic traffic state, achieves the best in delay, jitter and network utilization.